Adjunctive nutrients in first‐episode psychosis: A systematic review of efficacy, tolerability and neurobiological mechanisms. Issue 5 (21st March 2018) - Firth, Joseph; Rosenbaum, Simon; Ward, Philip B.; Curtis, Jackie; Teasdale, Scott B.; Yung, Alison R.; Sarris, Jerome
Abstract : Aim: The effects of nutrient‐based treatments, including adjunctive vitamin or antioxidant supplementation, have been explored extensively in long‐term schizophrenia. However, no systematic evaluation of trials in "first‐episode psychosis" (FEP) has been conducted, despite the potential benefits of using these treatments during the early stages of illness. Therefore, we aimed to review all studies examining efficacy, tolerability and the biological mechanisms of action, of nutrient supplementation in FEP. Methods: A systematic review of electronic databases was conducted from inception to July 2017. All information on feasibility, clinical outcomes and mechanistic findings from nutrient supplementation clinical trials was extracted and systematically synthesized. Results: Eleven studies with a total of 451 patients with FEP (from 8 independent randomized controlled trials) were eligible for inclusion. Six studies examined omega‐3 fatty acids, with inconsistent effects on psychiatric symptoms. However, mechanistic studies found significant improvements in hippocampal neuronal health and brain glutathione. Antioxidants "n‐acetyl cysteine" ( n = 1) and vitamin C ( n = 2) also improved oxidative status in FEP, which was associated with reduced psychiatric symptoms. No benefits were found for vitamin E ( n = 1). Finally, one study trialling the amino acid taurine, showed significant improvements in positive symptoms and psychosocial functioning. Conclusion: There is preliminary evidence that taurine improves outcomes in FEP, whereas effects of omega‐3 and antioxidant vitamins/amino‐acids are inconsistent; perhaps mainly benefitting patients with high levels of oxidative stress. Future studies should evaluate multifaceted dietary and supplementation interventions in FEP; targeting‐specific nutritional deficits and the range of aberrant biological processes implicated in the disorder.